Pelatihan Dan Pendampingan Kompetensi SDM BUMDes Dan Pelaku UMKM Untuk Meningkatkan Jejaring Usaha Di Desa Sindangsuka - Muizu, Wa Ode Zusnita; Dara Sagita Triski; Dara, Dara Sagita Triski (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
Community Service Activities (PPM) aim to develop the local economy in Sindangsuka Village, Garut Regency, with a focus on strengthening the role of BUMDes and MSME actors in the field of business management. The PPM program is implemented to increase the competency and capacity of village communities in various aspects of focus, including Human Resources (HR) development, marketing, production and business network development. The results of the second year of PPM activities (2024) show progress in several aspects. First, good communication was established between the PPM implementing lecturer, the Adhigana Restaurant Manager (Padjadjaran University Business Unit), and the Director of village-owned enterprises (BUMDes) Sindangsuka, which aims to establish cooperation in the organic catfish business network with the Adhigana Restaurant. This program adopts a more directed and focused approach based on evaluations and feedback from previous years. The results of outreach activities through training for MSME entrepreneurs highlight the importance of developing competencies in marketing, production and human resources as well as the need for collaboration between business actors to achieve inclusive and sustainable local economic development goals. In order to overcome local economic challenges, comprehensive efforts are needed, such as building digital infrastructure, establishing networks and collaboration, supporting product development, developing